The relationships between paediatric nurses' social support, job satisfaction and patient adverse events - Haitham Khatatbeh; Tariq Al‐Dwaikat; András Oláh; David Onchonga; Sahar Hammoud; Faten Amer; Viktória Prémusz; Annamária Pakai (Wiley, 2021)
Abstract Aims To explore the relationships of family, co‐worker and manager support with paediatric nurses' satisfaction and their perception of adverse events. Furthermore, this study aimed to assess the job satisfaction, social support and the perceived patient adverse events. Design This study used a cross‐sectional correlational design. Methods A convenient sample of 225 paediatric nurses was selected from nine hospitals in Jordan. Both the Pearson correlations and multiple regression tests were used in the analysis. The study was prepared and is reported according to the STROBE checklist. Results Significant and positive correlations were found between paediatric nurses' job satisfaction and the social support they receive. Significant negative correlations were also found between adverse events and both family and manager support. The multiple regression results showed that manager support is a significant negative predictor of both pressure ulcers and patient falls, and family support significantly predicted paediatric nurses' job satisfaction.